TOWARDS A NEW COMPREHENSION OF MODERNITY ACCORDING TO CHARLES TAYLOR. A NARRATION OF CHANGES IN THOUGHT - Martínez Pérez, Francisco Javier (2023)
In his works, Charles Taylor delves into his master narrative of Modernity as an alternative to the story of subtraction that became the dominant narrative. The study presented here only intends to delve into one of the causes that led to secularization; that is, the progressive disenchantment of the world. In his main works, the Canadian hermeneutic considers what other reasons led to alternative moral sources to theism and allowed the arrival of the coated self and exclusive humanism.